Cellular and Molecular Immunology Approaches for the Development of Immunotherapies against the New Coronavirus (SARS-CoV-2): Challenges to Near-Future Breakthroughs. (22nd December 2020) - Melgaço, Juliana Gil; Brito e Cunha, Danielle; Azamor, Tamiris; da Silva, Andrea Marques Vieira; Tubarão, Luciana Neves; Gonçalves, Rafael Braga; Monteiro, Robson Q.; Missailidis, Sotiris; da Costa Neves, Patricia Cristina; Ano Bom, Ana Paula Dinis
Abstract : The severe acute respiratory syndrome caused by the new coronavirus (SARS-CoV-2), termed COVID-19, has been highlighted as the most important infectious disease of our time, without a vaccine and treatment available until this moment, with a big impact on health systems worldwide, and with high mortality rates associated with respiratory viral disease. The medical and scientific communities have also been confronted by an urgent need to better understand the mechanism of host-virus interaction aimed at developing therapies and vaccines. Since this viral disease can trigger a strong innate immune response, causing severe damage to the pulmonary tract, immunotherapies have also been explored as a means to verify the immunomodulatory effect and improve clinical outcomes, whilst the comprehensive COVID-19 immunology still remains under investigation. In this review, both cellular and molecular immunopathology as well as hemostatic disorders induced by SARS-CoV-2 are summarized. The immunotherapeutic approaches based on the most recent clinical and nonclinical studies, emphasizing their effects for the treatment of COVID-19, are also addressed. The information presented elucidates helpful insights aiming at filling the knowledge gaps around promising immunotherapies that attempt to control the dysfunction of host factors during the course of this infectious viral disease.